Advances in Internal Combustion Engines and Fuel Technologies 2013
DOI: 10.5772/55495
|View full text |Cite
|
Sign up to set email alerts
|

Premixed Combustion in Spark Ignition Engines and the Influence of Operating Variables

Abstract: Advances in Internal Combustion Engines and Fuel Technologies 4 . . Overview of flame propagation mechanismDetailed observations of development and structure of the flame in SI engines can be made by using direct photographs or other methods such as Schlieren and shadowgraph photography techniques [ , ]. The initial stage of the combustion process is the development of a flame kernel, centred close to the spark-plug electrodes, that grows from the spark discharge with quasispherical, low-irregular surface its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…As clearly suggested by the COV data, a strong intake-to-exhaust pressure differential enables considerable internal burned gas recirculation and high levels of cylinder charge dilution; virtually, any valve overlap duration in excess of 30 CA deg results in degraded combustion and worsened fuel economy. As early IVO and late EVC are reported to exert similar influence upon charge dilution at low engine load[6], the experimental data suggest the effects of increased effective expansion ratio (more work extracted per cycle) would be more significant than those associated to increased effective compression ratio. As the engine speed is increased at low load for engine B(Figure 5), the overlap duration reduces in real time, limiting the amount of internal recirculation; here combustion regains stability and further retarding the EVC timing becomes beneficial.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…As clearly suggested by the COV data, a strong intake-to-exhaust pressure differential enables considerable internal burned gas recirculation and high levels of cylinder charge dilution; virtually, any valve overlap duration in excess of 30 CA deg results in degraded combustion and worsened fuel economy. As early IVO and late EVC are reported to exert similar influence upon charge dilution at low engine load[6], the experimental data suggest the effects of increased effective expansion ratio (more work extracted per cycle) would be more significant than those associated to increased effective compression ratio. As the engine speed is increased at low load for engine B(Figure 5), the overlap duration reduces in real time, limiting the amount of internal recirculation; here combustion regains stability and further retarding the EVC timing becomes beneficial.…”
mentioning
confidence: 77%
“…At low engine speed, wide overlaps are generally detrimental, yielding higher residual gas fraction [8] which may significantly degrade the combustion stability. Improvements in Brake Specific Fuel Consumption (BSFC) of up to 10%, as a result of early Intake Valve Opening (IVO) strategies, have been reported in recent studies [9,10]; these explain the observed changes referring to the displacement of fresh mixture with residuals during valve overlap, ultimately reducing the need for throttling [6]. If the intake cam profile is fixed, the effects of IVO are inevitably linked to those of Intake Valve Closing (IVC) timing.…”
Section: Variable Camshaft Timingmentioning
confidence: 99%
See 1 more Smart Citation